2019
DOI: 10.1038/s41467-019-09734-5
|View full text |Cite
|
Sign up to set email alerts
|

AURKB as a target in non-small cell lung cancer with acquired resistance to anti-EGFR therapy

Abstract: Non-small cell lung cancer (NSCLC) tumors harboring mutations in EGFR ultimately relapse to therapy with EGFR tyrosine kinase inhibitors (EGFR TKIs). Here, we show that resistant cells without the p.T790M or other acquired mutations are sensitive to the Aurora B (AURKB) inhibitors barasertib and S49076. Phospho-histone H3 (pH3), a major product of AURKB, is increased in most resistant cells and treatment with AURKB inhibitors reduces the levels of pH3, triggering G1/S arrest and polyploi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
76
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(82 citation statements)
references
References 50 publications
5
76
0
1
Order By: Relevance
“…Here, all of the mutual interactors of Survivin exhibited significant regulation, which led to a reduced expression of these molecules in Pirfenidone treated A549 cells ( Figure 4B). Furthermore, Survivin/BIRC5 interacted closely with molecules ( Figure 4C) which were shown to regulate stem cell properties in lung adenocarcinomas (SPC25) (28), influence radiosensitivity in lung cancer (AURKA) (29), or mediate anti-EGFR therapy in NSCLC (AURKB) (30). Interestingly, a majority of Survivin interacting molecules that were found to be significantly regulated by Pirfenidone are also associated with the mitotic spindle (MAD2L1, BUB1, BUB1B, BUB3, CDC20) and were shown to be increased in human breast cancer (31).…”
Section: Pirfenidone Down-regulated Survivin Affected Apoptotic Signmentioning
confidence: 99%
“…Here, all of the mutual interactors of Survivin exhibited significant regulation, which led to a reduced expression of these molecules in Pirfenidone treated A549 cells ( Figure 4B). Furthermore, Survivin/BIRC5 interacted closely with molecules ( Figure 4C) which were shown to regulate stem cell properties in lung adenocarcinomas (SPC25) (28), influence radiosensitivity in lung cancer (AURKA) (29), or mediate anti-EGFR therapy in NSCLC (AURKB) (30). Interestingly, a majority of Survivin interacting molecules that were found to be significantly regulated by Pirfenidone are also associated with the mitotic spindle (MAD2L1, BUB1, BUB1B, BUB3, CDC20) and were shown to be increased in human breast cancer (31).…”
Section: Pirfenidone Down-regulated Survivin Affected Apoptotic Signmentioning
confidence: 99%
“…Finally we could show the importance of CDK2 as a master regulator of many kinases and transcription factors such as MYC, AURKB, E2F4 and consequently TP53 and ATM activities ( Figure 4 D ). In particular, AURKB, which directly controls TP53 and ATM activities, appears to be a promising marker of kidney cancer [46][47][48] .…”
Section: Discussionmentioning
confidence: 99%
“…AURKB is also involved in resistance to specific anti-tumor agents, such as paclitaxel in NSCLC 45 . Bertran-Alamillo et al revealed that AURKB is related to acquired resistance to EGFR TKIs, and AURKB can become a potential biological target for anti- EGFR therapy of NSCLC without carrying resistance mutations 46 .…”
Section: Discussionmentioning
confidence: 99%